Réflexions autour du projet de bibliographie des éditions lyonnaises du seizième siècle (BEL16) - Mouren, Raphaële (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2011)
In November 2007, l’École nationale supérieure des sciences de l’information et des bibliothèques—France’s national school for information and librarianship—launched an ambitious project, following William Kemp’s proposal: establishing, in electronic form, an exhaustive, retrospective bibliography of books printed at Lyons during the sixteenth century. The implementation of this project was the object of numerous reflections, mostly upon the way the history of the book and the history of philology complement each other. Professional and disciplinary specificities concerned the identification of the types of users of such a base, the needs of these users, the norms regularly used, and the different levels of description considered to be necessary. This article recounts these conceptual progressions as they helped define bibliography in the twenty-first century. With precise comparisons to existing databases, and with concise and detailed definitions of methodology and issues, the author exposes the necessary decisions required of any bibliographic undertaking. Public, descriptions, corpus, standardization, and use are approached with reference to both conception and concept.